Exploring the Usability and Acceptability of a Well-Being App for Adolescents Living With Type 1 Diabetes: Qualitative Study - Katie Garner; Hiran Thabrew; David Lim; Paul Hofman; Craig Jefferies; Anna Serlachius (JMIR Publications, 2023)
Abstract BackgroundAdolescents living with either type 1 diabetes (T1D) or type 2 diabetes (T2D) have an increased risk of psychological disorders due to the demands of managing a chronic illness and the challenges of adolescence. Psychological disorders during adolescence increase the risk of suboptimal glycemic outcomes and may lead to serious diabetes-related complications. Research shows that digital health interventions may increase access to psychological support for adolescents and improve physical and mental health outcomes for youth with diabetes. To our knowledge, there are no evidence-based, publicly available mental health apps with a focus on improving the psychological well-being of adolescents with diabetes. ObjectiveThis study aimed to explore the acceptability and usability of our evidence-based well-being app for New Zealand adolescents, Whitu: 7 Ways in 7 DaysWhituWhituWhitu MethodsA total of 34 participants, comprising 13 adolescents aged 12-16 years (11 with T1D and 2 with T2D), 10 parents, and 11 health care professionals, were recruited from a specialist diabetes outpatient clinic and Facebook diabetes groups. Each participant attended one 1-hour focus group on Zoom, in person, or via phone. Researchers gathered general feedback on what makes an effective and engaging app for adolescents with diabetes, as well as specific feedback about Whitu ResultsAdolescents with T1D, their parents, and health care professionals found Whitu ConclusionsThere appears to be sufficient openness to the use of an app such as WhituWhituLIFT: Thriving with DiabetesLIFT